Sequential development of embryoblast-like memory entities in human cancer tissues: an evolutionary self-repair structure with pluripotentiality (2022)
Hidden collective organization of cancer cells can partially or completely return to embryoid genotype-phenotype with the plasticity to transform their morphology on cell embryoblast-like memory entities by expression of dormant genes that arise from embryogenesis. After hundreds of driver mutations, cancer cells gain new abilities or attributes and recapitulate early stages of embryogenesis. Our findings document how malignant tissues reactivated ancestral storage memory and elaborate inside tumor glands spiral-pyramidal-fractal chiral crystals (Tc) as geometric attractor proteins and biomimicry the primitive cellular blastocyst embryoblast fluid-filled cavity. The resultant evolutionary embryoblast-like entity has higher survivability and spatial cephalic-caudal growth organization with pluripotentiality that carry the correct DNA instructions to repair, and regenerate. The isolation and manipulation of these order structures can guide and control the regenerative pathway mechanism in human tumors as follows: modify and reprogram the phenotype of the tumor where these entities are generated, establish a reverse primordial microscopic mold to use the swirlonic collective behavior of cellular building blocks to regenerate injured tissues, convert cancer cells to a normal phenotype through regeneration using the organizational level and scale properties of reverse genetic guidance, global control of mitotic activity and morphogenetic movements avoiding their spread and metastasis, determining a better life prognosis for patients who incubate these entities in their tumors compared to those who do not express them. An emergent self-repair order structure, biological template can develop targeted therapeutic alternatives not only in cancer but also in treatment of autoimmune, viral diseases, and in regenerative medicine and rejuvenation.